2018
DOI: 10.3389/fnmol.2018.00288
|View full text |Cite|
|
Sign up to set email alerts
|

Dysregulation of MicroRNAs and Target Genes Networks in Peripheral Blood of Patients With Sporadic Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive and fatal neurodegenerative disease. While genetics and other factors contribute to ALS pathogenesis, critical knowledge is still missing and validated biomarkers for monitoring the disease activity have not yet been identified. To address those aspects we carried out this study with the primary aim of identifying possible miRNAs/mRNAs dysregulation associated with the sporadic form of the disease (sALS). Additionally, we explored miRNAs as modulating factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
111
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 83 publications
3
111
1
2
Order By: Relevance
“…Haramati et al reported that this micro-RNA is down-regulated in the genetic model of spinal muscular atrophy, which suggests its role in the development of neurodegeneration [75]; therefore, its increase in the environment of CNS may have beneficial influence on neural cells. Using high-throughput next-generation sequencing, Liguori et al showed that miR-let-7f-5p is down-regulated in peripheral blood of sALS patients [69]. Similar findings were reported by Takahashi et al, this time after analysis of ALS patients' plasma samples.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Haramati et al reported that this micro-RNA is down-regulated in the genetic model of spinal muscular atrophy, which suggests its role in the development of neurodegeneration [75]; therefore, its increase in the environment of CNS may have beneficial influence on neural cells. Using high-throughput next-generation sequencing, Liguori et al showed that miR-let-7f-5p is down-regulated in peripheral blood of sALS patients [69]. Similar findings were reported by Takahashi et al, this time after analysis of ALS patients' plasma samples.…”
Section: Discussionsupporting
confidence: 65%
“…In our previous study, we found consistent expression of several tested miRNAs in CSF and plasma of ALS patients [23]. miRNA-16-5p downregulation was shown in ALS patients compared to controls [68,69] and in a murine model of early-onset Alzheimer's disease (AD) [39]. Liu et al suggested a neuroprotective role of miRNA-16-5p since, upon administration of miR-16-5p into the brains of AD mice, amyloid precursor protein levels were reduced [39].…”
Section: Discussionmentioning
confidence: 59%
“…We thank Madadi and Soleimani for having cited our study; however, we respectfully disagree with their conclusion, which asserts that the customized miRNA normalization panel used by Raheja et al . may not be suitable, as miRNA normalizers showed dysregulated expression in other studies.…”
contrasting
confidence: 58%
“…In our cited study, we investigated the miRNA expression profile in blood samples of ALS patients using a high‐throughput next‐generation sequencing (HT‐NGS) approach, followed by quantititative polymerase chain reaction (qPCR) validation. Because there are no published studies that systematically evaluated reference miRNAs to normalize blood‐derived miRNAs in the setting of ALS, 5 candidate endogenous reference miRNAs were selected from previous qPCR blood studies and from suggested miRNA endogenous controls in the TaqMan Advanced miRNA Assays white paper (Applied Biosystems, Thermo Fisher Scientific).…”
mentioning
confidence: 99%
“…The statistical significance was determined using the one-tailed Fisher's exact test followed by the Benjamini correction; adjusted p-value <0.05 was set as the threshold value. Details of methods and software used for the analysis have been already published (Liguori, Nuzziello, Introna, et al, 2018a;Liguori, Nuzziello, Licciulli, et al, 2018b).…”
Section: Target Genes and Pathway Analysismentioning
confidence: 99%